Host range expansion of Leucobacter holotrichiae: first evidence of mammalian infection and comparative genomic insights - Li, Yong Jian; Qi, Bo Rui; Cao, Shu Zhu; Zhang, Run Ze; Jiao, Long Ling; Zhou, Ming; Cai, Jin Chun; Du, Meng Ying; Li, Ke Shuang; Xiao, Chen Cheng; Qi, Ya Yin (Frontiers in Microbiology, 2025)
Leucobacter holotrichiae has previously been identified exclusively in insect hosts, with no reports of its presence in mammals. This study is the first to report the isolation of three L. holotrichiae strains (LH23001, LH23002, and LH23003) from mixed cultures of bovine actinomycotic abscesses in a large-scale dairy farm in Xinjiang, China. Phenotypic analysis revealed that these Gram-positive bacilli are non-spore-forming, non-flagellated, non-hemolytic, non-motile, and capable of biofilm formation. The isolates formed transparent membranous white colonies on modified Gao’s medium and could grow in BHI liquid medium containing 9% NaCl. Phylogenetic analysis based on 16S rRNA gene sequences and average nucleotide identity (ANI) further confirmed that these strains are most closely related to L. holotrichiae, with all strains exhibiting strong biofilm-forming ability. Intraperitoneal infection experiments in mice showed that infection induced pathological changes in multiple tissues: vacuolar degeneration of cardiomyocytes, mild steatosis of hepatocytes, focal necrosis of a small number of lymphocytes in the white pulp of the spleen, extensive granulocyte infiltration in the alveolar walls of lung tissue, and mild edema of renal tubular epithelial cells in the renal cortex. Whole-genome sequencing results indicated that the genome size of these strains ranges from 3.63 to 3.68 Mb with a GC content of 66.8–67.2%. They carry multiple antimicrobial resistance genes and virulence factors, and five complete prophages were predicted. Functional annotation results showed that the strains have annotated information in databases including NR, GO, eggNOG, Swiss-Prot, CAZy, CARD, and VFDB. This study expands the known host range of L. holotrichiae, systematically analyzes its biological characteristics and genomic features, and provides a theoretical basis for future research on this bacterium.